Efektivitas Konseling Kelompok Teknik Modeling Terhadap Peningkatan Efikasi Diri Pada Siswa MTs Negeri 9 Sleman - Puri, Lintang Waskita (Universitas Mathla'ul Anwar Banten, 2024)
The objectives to be achieved in this study are to determine the effectiveness of counseling modeling techniques on improving self-efficacy in students of MTs Negeri 9 Sleman. The type of research in this study is experimental research. The research design used in this study is quasi experiment. The form of design used is Non-equivalent Control Group Design. The study population was VIII grade students of MTs Negeri 9 Sleman consisting of 4 classes, totaling 125 students. The sampling technique in this study used purposive sampling. The criteria for determining the sample in this study were eighth grade students of MTs Negeri 9 Sleman, which indicated a low learning discipline problem. The data collection method uses a self-efficacy scale that has gone through an expert validation process. Data analysis using non-parametric statistics with Man Withney (U) and Wilcoxon tests. The results showed that the counseling of the modeling technique by combining live models and symbolic models proved effective for self-efficacy (sign = 0.027 <0.05). These results can be concluded that group counseling through effective modeling techniques on improving self-efficacy in students of MTs Negeri 9 Sleman